Multilingual Legal Drafting, Translators’ Choices and the Principle of Lesser Evil - Stefaniak, Karolina (Meta, 2013)
Usually the quality of EU translations is not a prominent topic in the public sphere, and when it is brought up as an issue, it is mostly criticized in the context of its allegedly high costs and the apparently low quality. The critics, however, are often unaware of the motives behind the particular translation choices, which they perceive as awkward, unusual or simply wrong. This article argues that these choices result from the particular position of translation in respect to the process of legal drafting in the EU and that of translators in respect to the draftspersons, which results not only in intellectual, but also in ethical dilemmas of the translators. It is further argued that what may be considered an error from an outsider’s point of view is actually a conscious choice made by a translator trying to reconcile various divergent interests.